Frequency of undiagnosed depression and anxiety in patients with Type 2 Diabetes Mellitus attended at the outpatient clinic of a General Hospital in Lima, Peru. - Rosas-Matías, Johan (2019)
Background: The populations of patients with Type 2 Diabetes Mellitus (DM2) generally have a higher frequency of psychiatric illnesses than the general population. Objective: To identify the frequency of undiagnosed depression and anxiety in patients with DM2 who attended the outpatient clinic of a general hospital in Lima. Material and methods: A descriptive, cross-sectional study was conducted on patients with DM2, among whom the presence of depression and anxiety was determined by using the Depressive Psychopathology Scale (EPD-6) and the Lima Anxiety Scale (LAS-20). Results: From 327 patients included in the study, 23.9% had depression, 32.7% anxiety and 7.95% suicidality, whereas 5.5% presented symptoms of both, depression and anxiety. Additionally, 17.94% of patients with depression, and 16.82% of those with anxiety presented evidence of suicidality. 39.9 % of women had anxiety compared to 16.7% of men (p <0.01). The median age of patients with depression was 59 years (IQT: 51-64) versus 62 years (IQT: 54-69) among patients without depression (p=0.038). Conclusions: Almost a quarter (23.9%) of the patients with DM2 had depression, and a third (33.7%) presented anxiety. In addition, female sex and age appear to be significantly related to anxiety and depression, respectively.